Dampak Kecocokan Tugas dan Teknologi terhadap Kinerja Mahasiswa dan Dosen Akuntansi (Studi Implementasi Jurnal Elektronik) - Dewi Kartika Sari (STIE Indonesia Banking School, 2016)
This research aimed to examine the extent to which availability sources of electronic journals (technology) meet (fit) with the task (needs) of accounting students and lecturer. Using students and lecturer of Faculty of Economics and Business University of Indonesia (FEB-UI) as the sample, this research also will examine whether the fit between task and technology can affect the use (utilization) of these technologies, and how they affect individual performance. The research used survey methodology and Structural Equation Model as data analysis techniques. The results showed that the characteristic of technology affects the fit of the task in a positive and significant influence. The lack of compatibility between task and technology positively and significantly affect the use of technology. And lastly, the task-technology fit, and the use of technologies together affect individual performance